Personnel contributions to UN and non-UN peacekeeping missions A public goods approach - Gaibulloev, Khusrav (2015)
Based on spatial panel regressions for 1990-2012, this article draws publicness differences between peacekeeping personnel contributions to UN and non-UN peacekeeping operations. The analysis shows that UN missions are much less responsive to personnel spillovers, derived from other contributors' peacekeepers, than is the case of non-UN missions. UN peacekeeping missions display either no response or free riding to these personnel spillovers, while non-UN missions indicate spillover complementarity. Moreover, a number of controls distinguish the two kinds of peacekeeping, where non-UN missions display income normality and UN missions' deployments increase with the number of concurrent peacekeeping missions. The latter suggests that some countries specialize in supplying UN peacekeepers as a money-making venture. The positive response to the population variable supports this conjecture for UN missions, because a greater population base provides the recruits for peacekeeping operations. Our spatial empirical analysis accounts for the endogeneity of peacekeeper spillovers. The article concludes with a host of robustness tests that account for the alternative classes of peacekeepers, African Union and ECOWAS missions, and other empirical variants.